The Altitude Attainment and Inclination Alignment for the Satellite Launched from Kourou Site - Cakaj, Shkelzen; Kamo, Bexhet; Agastra, Elson (Discoveries in Agriculture and Food Sciences, 2016)
The geostationary orbit is a circular orbit 35786 kilometers above the Earth's equator and following the direction of the Earth's rotation. Communications satellites are often placed in the geostationary orbit. The rockets are used to place the satellite in geostationary orbit. The main goal of the launching process is to enable the satellite to acquire the desired geostationary orbit space parameters. There are two methods applied for putting satellites in the geostationary orbit, the first one is when a rocket takes the spacecraft to a low Earth circular orbit and then towards geostationary transfer orbit, and by the second method, the low circular orbit is skipped and the satellite goes straight to geostationary transfer orbit. Because of too large distance from the Earth’s surface this placement to geostationary transfer orbit is not done at once. The location of Kourou at French Guiana is the launching site of France and also shared with ESA (European Space Agency). The launch process from Kourou site firstly places the satellite at geostationary transfer elliptical orbit, and then the orbit geostationarity is achieved through two phases, the first phase is the altitude attainment at 35786km and the second is the inclination to be aligned with equatorial plane. During the whole process, the needed satellite’s propellant mass must be minimized. Three thrusts apogee and nodal thrust method applied for the altitude attainment and then the inclination alignment for the satellite to be consolidated in geostationary orbit, which is launched from Kourou site, is simulated and analyzed within this paper.